2021
DOI: 10.5114/amsad.2021.109287
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction in COVID-19 patients. A review of cases in the literature

Abstract: IntroductionCOVID-19 is an ongoing pandemic that has lasted more than a year. Patients with multiple comorbidities such as diabetes, hypertension, and smoking have been shown to be at increased risk of a more severe course and lethal outcome. Since the disease can also lead to a hypercoagulable state, several cases of acute myocardial infarction (AMI) have also been recorded.Material and methodsWe searched PubMed/Medline for case reports of AMI occurring in COVID-19 positive patients using “acute myocardial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Systemic viral infections may generate plaque rupture and thrombosis [4,5]. Notably, patients with COVID-19 and ACS have rarely been described in reports [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic viral infections may generate plaque rupture and thrombosis [4,5]. Notably, patients with COVID-19 and ACS have rarely been described in reports [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, first of all, using the PubMed database [ 69 ], we characterized each of the 42 hippocampal DEGs (of tame versus aggressive rats) identified in this work ( Table 2 ), in terms of how downregulation or upregulation of their orthologous human genes can manifest itself in hypertension, as presented [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ,…”
Section: Resultsmentioning
confidence: 99%
“…The association described between COVID-19 and STEMI was published in multiple case reports, including most patients with different comorbidities such as diabetes and hypertension, who also had a mean age of 58.3 years, and usually presented with severe clinical symptoms of COVID-19 [ 4 ]. A case series reported by Bangalore et al identified 18 patients with COVID-19-related STEMI.…”
Section: Discussionmentioning
confidence: 99%